On the model for U Geminorum - Harwood, John Malcolm (Department of Astronomy, 2016)
The term cataclysmic variable comprises several types of variable star - novae, recurrent novae, dwarf novae; and to these we add the nova-like variables, stars which exhibit many of the characteristics of the novae but which have not been observed to erupt. U Geminorum, discovered by Hinds in 1855, is the nomotype of the dwarf novae. These stars are characterised by large, abrupt, temporary increases in brightness that occur erratically at intervals of ten days to a year or more. The dwarf novae are faint objects, few reaching 11th magnitude at maximum, whereas at minimum light most are fainter than 16th magnitude. Thus they are spectroscopically inaccessible to all but the largest telescopes. Conventional photometric techniques applied to these objects gave no information indicating their physical nature. The time-scale of the observations was so long that only the gross variations in brightness were detected. Much of the observing was undertaken by amateurs (Fig. 1), and from this work several of the basic features of this group have emerged.